Fostering a Smart Business Community: The Bluru Bangkit Sidoarjo(BBS) MSME Association: Pendampingan Smart Business Community Paguyuban UMKM Bluru Bangkit Sidoarjo (BBS) - Nurul Hasanah Uswati Dewi; Deny Hermansyah; Reza Tianto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving local and national economic growth, providing employment, and supporting household livelihoods. However, many MSMEs, especially those within the Bluru Bangkit Sidoarjo (BBS) Association, continue to face persistent challenges due to conventional business practices. Manual bookkeeping, non-standardized production processes, and the mixing of personal and business finances often lead to inefficiency, poor decision-making, and low competitiveness. This community service program aims to enhance the competitiveness and independence of BBS MSMEs by introducing production standardization and digital financial management through the FinTrack application. The program employs a combination of training sessions and tailored mentorship to equip MSME members with practical skills in production process management and digital financial operations. The initiative targets 80% adoption of Standard Operating Procedures (SOPs) in production and 75% independent utilization of FinTrack for financial recordkeeping. Early results show that MSME members demonstrate increased confidence, improved accuracy in bookkeeping, and greater consistency in product quality. This program aligns with the National Research Master Plan (RIRN) and supports several Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation, and Infrastructure). In the long term, this initiative is expected to strengthen business independence, foster innovation, and enhance the resilience of local economies through a sustainable Smart Business Community (SBC) model.